Peran Ulama dan Organisasi Islam dalam Mempertahankan Pendidikan Islam Masa Penjajahan Jepang - Asy’arie, Bima Fandi; Ardiansyah, Ahmad; Susanti, Septiani Selly; Fatimah, Siti; Permatasari, Ermanita (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
This study aims to determine the role of Islamic scholars in developing Islamic education, then analyze the contribution of the Islamic organization Nahdlatul Ulama (NU). This research method is a library study (library research) with historical documents (historical document research) with a qualitative approach. Data obtained from two search sources, “Google Scholar” and “ScienceDirect.” The discussion in this article identifies, first, the role of Islamic scholars in developing Islamic education, namely: managing Islamic boarding schools as centers of Islamic education; maintaining Islamic identity and nationalism; establishing and managing madrasas; teaching Islam informally; and helping maintain social stability. Second, the contribution of the Islamic organization Nahdlatul Ulama (NU) includes maintaining Islamic boarding schools as centers of Islamic education, developing a curriculum based on Islamic tradition, instilling a spirit of nationalism through education, establishing madrasas and non-formal educational institutions, and maintaining traditional Islamic educational networks. In addition to preserving religious heritage, these ulama and the NU organization taught the next generation about knowledge and a sense of nationalism, strengthening the foundation of Indonesian society during the colonial period.